Change of Outpatient Oral Surgery during the COVID-19 Pandemic: Experience of an Italian Center - Francesco Bennardo; Alessandro Antonelli; Selene Barone; Michele Mario Figliuzzi; Leonzio Fortunato; Amerigo Giudice (International Journal of Dentistry)
COVID-19, which appeared to originate in China in December 2019, has spread worldwide in a pandemic way. The aim of this work is to present a protocol to standardize the outpatient oral surgery activities through remote triage, diagnostic tests, protections, and precautions that allow to provide care while minimizing risk for both patients and surgeons. This article summarizes the clinical and surgical experience of the Oral Surgery Unit of the “Mater Domini” Hospital (Magna Graecia University of Catanzaro, Italy) during the COVID-19 pandemic. The application of a scrupulous triage protocol, the use of remote consultations to limit patients’ access to the clinic, and the correct use of PPE prevented transmission of the virus between patients and staff members.